Tungsten nanodot arrays patterned using diblock copolymer templates - Kang, Gil Bum; Kim, Seong-Il; Kim, Young Hwan; Park, Min-Chul; Kim, Yong Tae; Lee, Chang Woo (JAPAN SOC APPLIED PHYSICS, 2007)
Dense and uniformly distributed arrays of holes and nanodots were fabricated in silicon oxide and silicon. The holes were approximately 25 nm wide, 40 nm deep, and 60 nm apart. To obtain nano size patterns, self-assembling resists were used to produce a layer of uniformly distributed parallel cylinders of poly(methyl methacrylate) (PMMA) in a polystyrene (PS) matrix. The PMMA cylinders were degraded and removed by acetic acid rinsing to produce a PS mask for pattern transfer. The silicon oxide was removed by fluorine-based reactive ion etching (RIE). Selectively deposited tungsten nanodots were formed inside nano sized trenches by low pressure chemical vapor deposition (LPCVD). The tungsten nanodots and silicon trenches were 26 and 30 nm, respectively.
Keywords: SELF-ASSEMBLED MONOLAYERS; FILMS; ROUTE